A Methodology for addiction recovery in Advaita Vedanta - Vikram Singh, Shivendra (International Journal of Psychosocial Rehabilitation, 2023)
The common conception is that philosophy is an armchair endeavour. For many (Žižek 2023), the task of philosophy is just to provide the right kinds of questions to the sciences upon which they can develop further tools etc. The research will aim to show that it is not just the right kind of questions that philosophy can provide, instead, it can provide practical solutions as well. The research paper will primarily aim to showcase a methodology for addiction recovery based on the philosophy of Advaita Vedanta, which can be broadly applied to most kinds of addiction. The biggest problem with most kinds of addiction treatment programmes is relapse. So, can we devise a methodology which not only cures the problem of addiction but also provides aid in refraining from subsequent relapse?